Effect of COVID-19 pandemic on diagnosis and treatment of thyroid cancer in Brazil - Silveira, Vitor Bock; Schwengber, Wallace Klein; Hetzel, Guilherme Moreira; Zanella, André B.; Scheffel, Rafael Selbach; Maia, Ana Luiza; Dora, Jose Miguel (Frontiers in Endocrinology, 2022)
Introduction: The COVID-19 pandemic delayed the diagnosis, treatment, and followup visits of patients with thyroid cancer. However, the magnitude with which these restrictions affected the Brazilian health care is still unknown. Methods: Retrospective analysis of thyroid cancer-related procedures performed in the Brazilian public health system from 2019 to 2021. Data were retrieved from the Department of Informatics of the Unified Health System (DATASUS). The following procedures were evaluated: fine-needle aspiration biopsies (FNABs), oncologic thyroidectomies, and radioiodine (RAI) therapies for thyroid cancer. The year of 2019 served as baseline control. Results: Compared with 2019, FNABs, oncologic thyroidectomies, and RAI therapies performed in 2020 decreased by 29%, 17% and 28%, respectively. In 2021, compared with 2019, FNABs increased by 2%, and oncologic thyroidectomies and RAI therapies decreased by 5% and 25%, respectively. Most pronounced reductions were observed in the first months of the pandemic. In April 2020, FNABs decreased by 67%, oncologic thyroidectomies by 45%, and RAI therapies by 75%. In 2021, RAI therapies were the only procedure with statistically significant decrease. Conclusion: The restrictions to public health care during the COVID-19 pandemic resulted in a significant reduction in diagnostic and treatment procedures for thyroid cancer in Brazil. The effect of these transitory gaps in thyroid cancer care, due to COVID-19, are still unclear.